Social Security Survivors Benefits: The Effects of Reproductive Pathways and Intestacy Law on Attitudes. Issue 2 (26th June 2013) - Hans, Jason D.; Gillen, Martie
<x xml:space="preserve">Abstract</x> Most minor children are eligible for Social Security survivors benefits if a wage‐earning parent dies, but eligibility of children not in utero at the time of death is more nuanced. The purpose of this study was to examine attitudes concerning access to Social Security survivors benefits in the context of posthumous reproduction. A probability sample of 540 Florida households responded to a multiple‐segment factorial vignette designed to examine the effects of state intestacy laws and five reproductive pathways – normative, posthumous birth, cryopreserved embryo, cryopreserved gametes, and posthumous gamete retrieval – on attitudes toward eligibility for the Social Security survivors benefits. Broad support was found for the survivors benefits following normative and posthumous birth pathways, but attitudes were decidedly less favorable when the child was not in utero at the time of parental death. In addition, in stark contrast to the recent U.S. Supreme Court decision in Astrue v. Capato, the vast majority of respondents did not believe state intestacy laws should determine eligibility for Social Security survivors benefits.